พระเครื่องกับพระพุทธศาสนาในประเทศไทยปัจจุบัน - อภิวัฒน์ อรัญภูมิ (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
This thesis aimed to study the belief, concept, and faith of Thai Buddhists towards Buddhist votive tablets on the consistency with or the contrary to the Buddhism principles and to study the roles of Buddhist votive tablets on Thai society that were related to and affected Buddhism currently by studying the related information from Buddhism principles and analyzing with the Thai society s present circumstances together with information obtained from questionnaire in field survey. The research was done by involving three groups of sample that were the Buddhist votive tablet s sellers and collectors, the Buddhist monks-novices, and Thai Buddhists. It was found from the research that most of the sample considered the Buddhist votive tablets as the symbol and religious, auspicious objects; the beliefs in religion were different. Some believed that they could make a wish or request for fortune, they believed in miraculous power that could make them safe from various dangers; these were beliefs that were not consistent with the Buddhism principles. Also, it was found that Buddhist votive tablets played roles and influenced in believing in Buddhism in various forms; for example, it was the thing to mentally resort to in order to recall the triple gems (Buddha s teachings), to recall the Buddhism principle. And it was found that currently, Buddhist votive tablets were used as the products; they were widely traded in the market among those who like the Buddhist votive tablets; this situation was called "commercial Buddhism"; such situation appeared widely in all level of Thai society.